Exploração do trabalho das mulheres negras na base da acumulação do capital transnacional em Sergipe : o caso do setor de telemarketing - Freitas, Karla Maria Cardoso Araujo (2022)
This study analyzes the labor exploitation of black women at ALMAVIVA do Brasil Telemarketing e Informática S.A, located in the state of Sergipe. This is a literature research that used as its main source the lawsuits from the Regional Labor Court of the 20th Region (TRT-20), in which the Company is the defendant. The study sought to identify the various mechanisms of exploitation of women's work, through which ALMAVIVA guarantees the production of absolute and relative surplus value. In view of the case analyzed, it is possible to affirm that the capital accumulation of the mentioned transnational corporation is based on the overexploitation of black women workers. This dissertation focusing on the analysis of social issues attempted to understand the changes in labor relations and the struggles that were and are being implemented by black women against "capital".